1995
DOI: 10.1111/j.1525-1446.1995.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive and Organizational Model of Community as Client: A Model for Public Health Nursing Practice

Abstract: The Interactive and Organizational Model of Community as Client is presented as a conceptual framework for the specialty of public health nursing. A descriptive study was undertaken that explored a construct of the model, community-focused nursing. The study used a survey mailed to a stratified, random sample of directors of public health nursing (n = 145) in local health departments in an eight-state region of the midwestern United States. Seventy-nine percent (n = 115) of the directors responded. The vast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Despite the differences between the East and the West, in both regions PHNs have contributed to the promotion of health and well-being of individuals, families and community populations (World Health Organization, WHO 1996). Public health nursing practices are invisible and complex; previous studies show various theoretical models that focused on the role or practice of PHNs (Keller et al 1998, Kosidlak 1999, and their target population (Kuehnert 1995). In the USA, Quad Council of Public Health Nursing Organizations developed a set of core competencies for PHNs from 2000 (Quad Council of Public Health Nursing Organizations 2004).…”
Section: Background Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences between the East and the West, in both regions PHNs have contributed to the promotion of health and well-being of individuals, families and community populations (World Health Organization, WHO 1996). Public health nursing practices are invisible and complex; previous studies show various theoretical models that focused on the role or practice of PHNs (Keller et al 1998, Kosidlak 1999, and their target population (Kuehnert 1995). In the USA, Quad Council of Public Health Nursing Organizations developed a set of core competencies for PHNs from 2000 (Quad Council of Public Health Nursing Organizations 2004).…”
Section: Background Of This Studymentioning
confidence: 99%
“…We also found that the JPPHN Model identifies two types of care: PHNs directly supporting an individual or their family's health, and their role in developing resources in the community through collaborating with inhabitants and multidisciplinary professionals to promote community health. Many previous studies have focused on the role and skills of PHNs and their target population because PHNs' core function is providing family-centred care (Kuehnert 1995, Keller et al 1998, Kosidlak 1999, Smith 2004, Carr 2005. The Skills Council for Health in the UK ÔSkills for Health Project' covers a broad range of competencies relevant to public health, cancer treatment and clinical health for all public health practitioners.…”
Section: Comparison With Western Projects For Clarifying Phns' Practicementioning
confidence: 99%
“…Specific activities or competencies have been identified for community-focused nursing (Storfjell & Cruise, 1984;Kenyon et al, 1990;Kuehnert, 1995). These activities describe individuavfamilyklient oriented services but also emphasize community wide or aggregate planning and intervention services.…”
mentioning
confidence: 99%
“…However, funding in many cases continues to be provided categorically, limiting the ability to focus on the broad determinants of health and the underlying reasons for poor health (Conley, 1995; Gebbie, 1995; Kuss, Proulx‐Girouard, Lovitt, Katz, & Kennelly, 1997). It is within this milieu that PHN is challenged to reinvigorate a practice aimed at improving health at the community and systems levels as well as assisting individuals and families in improving their quality of life (Diekemper et al., 1999a,b; Kuehnert, 1995; McKnight & Van Dover, 1994). Clarification of PHN roles and practice assists in the appropriate use of public health nurses, which is an acute concern in this era of impending nursing shortage (Buerhaus, 1998; Coffman & Spetz, 1999; Kilborn, 1999).…”
mentioning
confidence: 99%
“…Creation of a PHN model provides a relevant framework to conceptualize changing roles and practice (Nicoll, 1997). Different models have been presented to guide PHN practice (American Nurses' Association, 2000; Anderson & McFarlane, 2000; Conley, 1995; Olson Keller, Strohschein, Lia‐Hoagberg, & Schaffer, 1998; Kosidlak, 1999; Kuehnert, 1995; Kuss et al., 1997). The purpose of this article is to describe the Los Angeles County Public Health Nursing (LAC PHN) Practice Model, its origins, and its application.…”
mentioning
confidence: 99%